Construing motherhood across generations in Taiwan’s social transition: associations with depression and somatic symptoms - Lin, YuChi (Frontiers in Psychology, 2026)
This study explores how Taiwanese mothers from two generations construe motherhood and how these constructions relate to depression, somatisation, and social functioning. Drawing on Personal Construct Psychology and using the repertory grid technique as a semi-structured assessment tool, the study compares mothers born before and after 1987—a pivotal year marking the lifting of martial law and the shift toward democratic, individualised parenting norms. Quantitative findings reveal distinct generational portraits. For older mothers, the public self is central; distress is linked to the pressure to maintain consistency between public performance and private reality, and unresolved intergenerational tensions are often expressed through somatic symptoms. In contrast, younger mothers exhibit significantly higher tightness of construing and construe their child as significantly closer to their ideal self, suggesting the child is central to their ideal identity. Their distress arises primarily from discrepancies between their private self and high internal standards. Additionally, household income was significantly correlated with mental health only for younger mothers, suggesting that financial resources function as a subjective condition for coping with intensive parenting demands. The study highlights how generational shifts influence the vulnerabilities of caregiving, suggesting that policy support for the younger generation should go beyond financial subsidies to focus on bolstering social networks.